Formulasi dan Evaluasi Emulgel Ekstrak Rimpang Jeringau (Acorus calamus L.) sebagai anti-acne - Rusdiati Helmidanora; Yullia Sukawaty; Husnul Warnida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Dermatology studies in Indonesia show an increase in acne vulgaris incidents with the highest prevalence in adolescents. Acne topical therapy generally contains retinoids. However, this therapeutic option has drawbacks, namely burning sensation, dry skin, erythema, and itching of the skin. Along with people's interest in using natural products, alternative therapies with natural products are increasingly having economic value. One of the natural ingredients that have the potential to be anti-acne is Acorus calamus L. Sweet pea (Acorus calamus L.) is a plant whose leaves and rhizomes are used empirically by the Dayak tribe in Borneo to treat skin diseases. Acorus calamus rhizome ethanol extract can inhibit the growth of Propionibacterium acnes bacteria that predominate in acne inflammation. Acorus calamus rhizome extract in this study was formulated in the form of an emulgel because it effectively delivers hydrophobic active substances. Emulgel is also not greasy but moisturizes the skin. The research aimed to produce an anti-acne emulgel formulation from Acorus calamus extract as a natural raw material that meets the physical stability requirements. The research was conducted at the Phytochemical Laboratory, Pharmaceutical Technology Laboratory, and Microbiology Laboratory of Samarinda School of Health Sciences. The research stages are the preparation of plant extract, phytochemical analysis, preparation of emulgel, evaluation of emulgel, and antibacterial activity assay. The Emulgel formulation was carried out with variations in the concentration of the gelling agent, namely Carbomer 940 0.5% (Formula A), 0.75% (Formula B0, and 1% (Formula C). The results of the physical evaluation showed all formulas met the requirements of the organoleptic test, homogeneity test, pH test, spreadability test, and viscosity test. All formulas have non-Newtonian flow types with plastic properties. The antibacterial test results show that all formulas can inhibit the growth of Propionibacterium acnes bacteria.